Nurses perception, attitudes and preferences in using electronic documentation in a public hospital, Selangor - S., Noor Hafizah; Lee, Khuan (Community Health Society Malaysia, 2018)
Background: Electronic documentation consists of electronic care plans and nursing, classification as well as all aspects of patient care from charting admissions to discharge. The aim of the study is to determine the perceptions, attitudes, and preferences of nurses, as well as other factors related to the use of electronic documentation. Materials and Methods: A cross-sectional design was used in this study. The data were collected from March until May 2017 using self-administered questionnaires; 95 nurses working in medical and surgical wards at a public hospital participated. P<0.05 was considered to be statistically significant, and data analysis was performed using IBM SPSS version 21. Result: A total of 95 respondents participated in the study. The findings of this study showed that 61.1% had a positive attitude. The majority were female (90.5%). Among the respondents, 81.1% were aged ≤30 years old; 69.5% had ≤6 years working experience as a staff nurse; 43.2% had computer education, and 61.1% had previously received computer training. There were associations between computer education (p<0.011), computer training (p<0.048), and positive attitude. Conclusion: The majority of the respondents had a positive attitude towards the use of electronic documentation. Electronic documentation should be included in formal nursing education to inculcate a positive attitude to electronic handover communication, which directly improves the quality of patient care.